A 6-Month Exercise Intervention Among Inactive and Overweight Favela-Residing Women in Brazil : The Caranguejo Exercise Trial - Alves, João G. (American Public Health Association, 2009)
Objectives. We examined the viability and efficacy of a known quantity of exercise in facilitating weight loss among previously sedentary or irregularly active overweight and obese adult women residing in a slum (favela) in Brazil. Methods. In this randomized controlled trial, 156 women were randomized to a control or intervention group (78 in each group). Exercise was supervised, consisting of three 50-minute aerobic sessions each week for 6 months. Results. Ninety-one percent (71) of the participants in the intervention group completed 6 months of the exercise program. At 6 months, women in the treatment group showed significant reduction in weight (mean = −1.69 kg; 95% confidence interval [CI] = −2.36,−1.03) and body mass index (mean = −0.63 kg/m(2); 95% CI = −0.97, −0.30) compared with controls (P for both < .001). Conclusions. A moderately intense, structured exercise program resulted in modest weight loss in women when sustained for 6 months.